The Role of Electronic Evidence in Proving Digital Gambling Crimes Study of PWT Decision - Sinaga, Chrismansyah; Zuliah , Azmiati; Maysarah , Andi (Tasyri' : Journal of Islamic Law, 2026)
The advancement of information technology has contributed to the emergence of digital-based crimes, including online gambling. In criminal proceedings, electronic evidence plays a crucial role in establishing the occurrence of such offenses. This study aims to analyze the legal position of electronic evidence within the Indonesian criminal evidentiary system, its application in Decision Number 1/Pid.B/2025/PN PWT, and the judge’s considerations in assessing its probative value. This research employs a normative legal method using statutory and case approaches. The findings indicate that electronic evidence is legally recognized under the Law on Electronic Information and Transactions and is regarded as an extension of evidentiary instruments regulated in the Criminal Procedure Code. In the analyzed decision, screenshots, digital communications, and electronic transaction records significantly contributed to proving the elements of gambling offenses. The court evaluated the evidence based on its legality, authenticity, and correlation with other admissible evidence within the negative statutory system of proof.